Students’ Perceptions on The Impact of Artificial Intelligence on English Grammar Learning - Awalin, Arpinda Syifa'a; Iftanti, Erna; Umami, Muhammad Sulung Mufty (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
Artificial Intelligence (AI) has made significant strides in various fields, including language-related tasks and educational applications. This study explores students' perceptions of the impact of Grammarly, an AI-powered writing assistant, on English grammar. Grammarly provides users with grammar and spelling correction, style suggestions, and writing enhancements. By investigating students' attitudes, experiences, and opinions regarding Grammarly, valuable insights can be gained into how this AI technology influences English grammar learning and writing proficiency. Through a mixed-methods approach involving surveys and interviews, data were collected from a diverse group of students across different educational institutions. The findings reveal multifaceted perspectives, highlighting the advantages, challenges, and implications of incorporating Grammarly as a grammar tool in language education. This research contributes to the existing knowledge on the integration of Grammarly and similar AI technologies, providing practical insights for educators, policymakers, and AI developers seeking to enhance English grammar instruction through innovative AI tools